Modelação matemática e alfabetização científica da educação básica - Selong, Lisiane Milan (2013)
This Master thesis was aimed at analyzing the scientific alphabetization of students in primary and secondary education through the Mathematical Modeling in Education. The methodological procedures are divided into four stages, called maps, to know: Identification Map, Theoretical Map, Field Map and Analysis Map. Identification Map contains: data and information justifying the theme choice, the presupposition, identification of the problem, research questions, objectives and methodological procedures. Theoretical map shows the theories that supported the research concerning: Mathematical Modeling, Mathematical Modeling in Education, Scientific Alphabetization and Scientific Literacy. In the field map was performed the elaboration and application of didactic material for the collection of data and the organization of the collected materials. The data collection occurred in two stages: initially did application with four classes of first year of high school - totaling 122 students from a school in the interior of Rio Grande do Sul, being the teacher the author of this research; in sequence, was performed its modeling application with a group of volunteer students from sixth grade elementary in the same school group previous in extra-time class - this group started with 15 students and 9 concluded the activities. In analysis map was performed qualitative analysis of the data and made the interaction between the theoretical map and field map, which enabled to verify in which levels of scientific alphabetization students were in the three phases of modeling. It was found that students did not qualify only at a level during the modeling and have shown progress during the three phases of modeling.